Layanan Daring Perpustakaan Perguruan Tinggi dan Sikap Terhadap Kepuasan Mahasiswa Pada Masa Pandemi COVID-19 di Provinsi Riau - Thamrin Hasan; Agus Rifai (Perpustakaan Nasional, 2021)
The purpose of this study was to determine the effect of online library services and attitudes on student satisfaction. Either partially or simultaneously. Using a survey method with correlational techniques. Respondents were 300 students taken from 20 universities, using quota sampling technique. The research instrument used a questionnaire, Likert scale model. The data analysis technique used is descriptive statistical analysis techniques and inferential statistics. The results showed that: (1) There was an effect of online services on student satisfaction, with a correlation coefficient (r) of 0.275. This shows that the strength level of the relationship is weak. And the coefficient of determination R Square (r2) 0.073. This means that the effect of variable X1 on Y is only 7.30%. (2) There is no influence of student attitudes on satisfaction, the correlation coefficient (r) is 0.005. This shows the level of strength of the relationship is very weak. And the coefficient of determination R Square (r2) 0,000. This means that the variable X2 has no effect on Y (0.00%). (3) There is an effect of online library services and attitudes simultaneously on student satisfaction, with a multiple correlation coefficient (R) = 0.271. This shows that the level of strength of the relationship is simultaneously weak. The coefficient of determination R Square is 0.073, which means that the simultaneous influence of the variables X1 and X2 on student satisfaction is only 7.30%. The results of this study are very useful for the improvement and improvement of online library services, especially during the COVID-19 pandemic in Riau Province. The conclusion of this research shows that student satisfaction cannot be fulfilled properly if only seen from the aspects of online services and attitudes.